Waste profile and waste-to-energy conversion potential of medical, hazardous industrial, and electronic residual wastes in Metro Manila, Philippines - Manegdeg, Ferdinand; Rollon, Analiza; Magdaluyo, Eduardo Jr.; Ballesteros, Florencio Jr.; de Sales-Papa, Louernie; Clemente, Eligia; Macapinlac, Emma; Ibanez, Roderaid; Cervera, Rinlee Butch (2021)
"Waste disposal is an important issue that needs to be addressed, not only for health and environmental reasons but also for its social and economic impacts. Three important waste streams that contribute to the growing amount of wastes generated come from medical, industrial, and electronic residual wastes. These residual wastes are usually just being dumped or disposed of in sanitary landfills. Apart from finding solutions to these environmental waste problems these wastes can be a possible source of energy that can support our energy sustainability. In this study, three different waste streams, medical, industrial, and electronic wastes in Metro Manila - the capital region in the Philippines - were profiled and investigated for their potential as waste-to-energy (WTE) feeds"-title page.
Includes bibliographical references.
Keywords: Electronic waste; Factory and trade waste -- Research; Medical wastes; Hazardous wastes